POTENTIAL ACTIVITY OF KAEMPFEROL AS ANTI-PARKINSON’S; MOLECULAR DOCKING AND PHARMACOPHORE MODELLING STUDY - MAHFUDIN, UMIL; SUBARNAS, ANAS; WILAR, GOFARANA; HERMANTO, FAIZAL (International Journal of Applied Pharmaceutics, 2023)
Objective: This study examined molecular docking and pharmacophore modeling to evaluate the potential antiparkinson activity of Kaempferol on various types and classes of receptors. Methods: The molecular docking was performed on various classes of receptors, namely transcription factor Nrf2, A2A Adenosine, and catechol-O-methyl transferase, using auto dock 4.0.1 software. Results: Kaempferol exhibited potential effects on two of the three tests (A2A adenosine and COMT receptors) as indicated by the lowest free energy binding values (-5.42 kcal/mol,-7.16 kcal/mol, and-8.33 kcal/mol, respectively). Kaempferol also had lower inhibitory constant values on transcription factor Nrf2, A2A adenosine, and COMT receptors (106.06 µM, 5.63 µM, and 779.51 nM, respectively). Kaempferol and the natural ligand had similar functional groups according to the critical components of the interaction between amino acid residues. The pharmacophore modeling revealed that hydroxyl functional groups strongly interact with crucial amino acid residues of the receptors. Conclusion: This study concludes that kaempferol is a potential antiparkinson agent against multiple receptors.